Spatial expansion pattern of black cherry Padus serotina Ehrh. in suburban zone of Białystok (NE Poland) - Wołkowycki, Dan; Próchnicki, Paweł (Biodiversity: Research and Conservation, 2016)
The object of the study is the distribution and spatial pattern of black cherry Padus serotina Ehrh. population and the impact of landscape structure on the expansion of this alien species in the suburban zone of the city, where the land-use has rapidly been transforming recently. The population of black cherry expands centrifugally, spreading from fringes of the city to outer zones of the agglomeration with more agricultural character. Individuals of P. serotina are distributed in clusters in this area. The maximum observed population density reaches 371/ha (mean 11.3/ha for colonized plots). The main factor influencing the landscape invasibility is cessation of agriculture. Although the first sources of spread of P. serotina are localities in forests, where 46% of the total number of individuals are concentrated, nevertheless, the largest group of juveniles (48%) was found on abandoned farmlands. Over 90% of all youngest individuals were recorded at a distance of up to 100 m from older ones. Chances of isolated occurrence are small and the probability of the colonization is strongly dependent on the occupation of adjacent areas by the species. Black cherry disperses, primarily, according to a spatial pattern of phalanxes, by occupying areas immediately adjacent to places previously colonized and then filling the available habitats. Long-distance dispersal seems to play a minor role for its expansion. Autocorrelation and diffusion models of spread should be taken into account in preventing further expansion of black cherry and planning conservation measures in natural protected areas.